First insight into Mycobacterium tuberculosis genetic diversity in Paraguay - Candia, Norma (2007)
Background: We present a picture of the biodiversity of Mycobacterium tuberculosis in Paraguay, an inland South American country harboring 5 million inhabitants with a tuberculosis notification rate of 38/100,000. Results: A total of 220 strains collected throughout the country in 2003 were classified by spoligotyping into 79 different patterns. Spoligopatterns of 173 strains matched 51 shared international types (SITs) already present in an updated version of SpoIDB4, the global spoligotype database at Pasteur Institute, Guadeloupe. Our study contributed to the database 13 new SITs and 15 orphan spoligopatterns. Frequencies of major M. tuberculosis spoligotype lineages in our sample were as follows: Latin-American & Mediterranean (LAM) 52.3%, Haarlem 18.2%, S clade 9.5%, T superfamily 8.6%, X clade 0.9% and Beijing clade 0.5%. Concordant clustering by IS6110 restriction fragment length polymorphism (RFLP) and spoligotyping identified transmission in specific settings such as the Tacumbu jail in Asuncion and aboriginal communities in the Chaco. LAM genotypes were ubiquitous and predominated among both RFLP clusters and new patterns, suggesting ongoing transmission and adaptative evolution in Paraguay. We describe a new and successfully evolving clone of the Haarlem 3 sub-lineage, SIT2643, which is thus far restricted to Paraguay. We confirmed its clonality by RFLP and mycobacterial interspersed repetitive unit (MIRU) typing; we named it "Tacumbu" after the jail where it was found to be spreading. One-fifth of the spoligopatterns in our study are rarely or never seen outside Paraguay and one-tenth do not fit within any of the major phylogenetic clades in SpoIDB4. Conclusion: Lineages currently thriving in Paraguay may reflect local host-pathogen adaptation of strains introduced during past migrations from Europe.